Proyecto de inversión para la implementación de un servicio de intermediación inmobiliaria interactivo a través de un portal en el web en la cuidad de Guayaquil - Neira Rivera, Hector Daniel (2009)
Home E-360 in conjunction with RENASCO is an Internet portal (initially started the business in Guayaquil’s city), which offers the option to individuals (home or abroad) or residential construction companies with projects that wishing to sell their homes efficiently and effectively, can do through us, offering an innovative marketing tool, which is displayed in 360 ° panoramic images, providing an interactive experience with pictures of houses for sale of all types This helps the customers can see the details of the properties offered without the need to mobilize, also providing all necessary information in detail for the customer interested in the properties can make your decision, supported by a complete counselling after the transaction, the client would be guided in all processes that are required for the purchase occur. We seek to obtain the property that best fit the needs and requirements of buyers, thus demonstrating that we genuinely interested in your needs, for those interested in purchasing this property must complete a form in which information is obtained from which we can mention: Type and size of housing square meters, number of bedrooms and bathrooms, price, location, ownership, among other variables.